Efflorescence of Alkali-Activated Cements (Geopolymers) and the Impacts on Material Structures: A Critical Analysis - Longhi, Márlon A.; Zhang, Zuhua; Rodríguez, Erich D.; Kirchheim, Ana Paula; Wang, Hao (Frontiers in Materials, 2019)
Even with the rapid development of the alkali-activated cement (AAC) technology in the past few years, some phenomena still needs to be better understood, that may alter the durability of the material. In many industrial uses and laboratory researches the formation of the salts on the surface alkali-activated type cements was observed, which was identified as efflorescence. This occurs due to the presence of an alkali transported in contact with the humidity and CO2 environment. It may present externally from the formation of salts on the surface and internally with the carbonation of the alkalis in capillary pores. The effects of efflorescence on the material in use, as well as all factors that can influence its formation are not yet fully understood or reported. The search for papers was conducted using the search words efflorescence and geopolymer/alkali-activated, combined in the electronic data base. Due to the limited quantity of papers published related to efflorescence in geopolymers, the review was complemented using papers that discuss this behavior in Portland cement (PC) and based on the main properties that can influence the formation of efflorescence. In this paper, to understand the nature of efflorescence, upon which proper methods of minimizing of this issue can be based, the following aspects are discussed and re-examined: (1) the development of efflorescence's in PC concrete, (2) the role of alkalis in AACs, (3) efflorescence in AACs, and (4) effect from a physical and microstructural point of view of efflorescence's on the ACCs. This paper highlights that the nature of the pore structure and the design parameters (such as alkali concentration, presence of soluble silicates, and water content in the activator) are the two most important factors that control efflorescence rate and changes in mechanical behavior. However, the stability of the alkalis and their relationship with the formed gel, which are determining factors in the formation of efflorescence, remain not completely understood. In the same way, the effect of efflorescence in tensile strength and shrinkage needs to be evaluated.